Thiotepa in combination with cisplatin for primary epithelial ovarian cancer: A phase II study. Issue 6 (1st October 2002) - Gordinier, M. E.; Kudelka, A. P.; Kavanagh, J. J.; Wharton, J. T.; Freedman, R. S.
Abstract : The objectives of this phase II protocol were: 1) to determine the clinical activity of thiotepa combined with cisplatin in suboptimally debulked advanced epithelial ovarian carcinoma as first-line chemotherapy, 2) to determine by surgery the response after 6 courses of chemotherapy, and 3) to identify the regimen's qualitative and quantitative toxicities. Patients with FIGO stage IIIC or IV epithelial ovarian cancer were eligible to receive cisplatin (50 mg/m 2 ) followed by thiotepa (40 mg/m 2 ) on an every 4-week schedule. Patients showing no evidence of disease after six cycles of chemotherapy underwent surgical reassessment. Thirty-one patients were evaluable for toxicity and response. Myelosuppression was the major toxicity and hematologic toxicities prompted all dose reductions. No growth factor support was given in this trial. Thirty-nine percent of patients (12/31) had a clinical complete response. Of these, 16% (5/31) had complete pathologic response and 19% (6/31) had partial pathologic response. One long-term survivor declined reassessment laparotomy. Including the 16% of patients with a partial response, the overall response rate was 55% (17/31). Five patients are currently alive 8 years after enrollment. Median survival was 16.8 months for all patients, 21.5 months for patients with partial response, and 60.8 months for patients with complete pathologic response. A normalization or >50% decrease in CA125 level occurred in 93% of patients. This study indicates that first-line treatment with thiotepa and cisplatin produces significant long-term responses when tumors are sensitive. Such treatment is a reasonable option when paclitaxel is not available.